Carbon Nanotubes: A Molecular Dynamics Study on Self‐Assembly of Single‐Walled Carbon Nanotubes: From Molecular Morphology and Binding Energy (Adv. Mater. Interfaces 19/2019). Issue 19 (9th October 2019) - Zhang, Jianwei; Cui, Jianlei; Cheng, Yang; Wang, Wenjun; He, Xiaoqiao; Mei, Xuesong
Abstract : The cover provides an insight into the adsorption behavior of modified single‐walled carbon nanotubes (SWNTs) on the functionalized surfaces. On the hydrophilic surfaces, the surfactant encapsulated SWNTs binds to the substrate through its hydrophilic end, while on the hydrophobic surface, the surfactant interacts with the substrate to separate itself from the SWNTs surface and make the assembly unable to complete. More details can be found in article number 1900983 by Jianwei Zhang, Jianlei Cui, and co‐workers.